خبرة مشفى الأسد الجامعي باللاذقية في تدبير سرطانة المثانة وذلك في الفترة ما بين 2005 – 2007 - يوسف, محمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 60 مريضاً (52 ذكر,8 إناث) لديهم ورم مثانة, متوسط أعمارهم 62.5 سنة, معظمهم من المدخنين الشرهين (70%), يشكون جميعاً من بيلة دموية 100% و لدى 75% أعراض بولية انسدادية. تم تشخيص جميع الحالات بتنظير المثانة حيث وجد لدى 58% أورام صغيرة ولدى 60% أورام متعددة.لوحظ وجود Ta وT1 و T2 و T3 – T4 لدى 36%و 31 % و 25% و 6.6% على الترتيب. أما درجات الأورام فكانت G1 و G2 و G3 لدى 38%,43%,18%. خضع 66%منهم لـ TUR وعلاج كيماوي مساعد ضمن المثانة بينما خضع 28% منهم لاستئصال مثانة جذري و 3% لاستئصال مثانة جزئي. أجري زرع حالبين على السين عند 7 مرضى بينما أجري تصنيع مثانة قويم عند 6 و زرع حالبين على الجلد عند اثنين و تصنيع مثانة مستمسك عند مريض وحيد و أجريت عملية بريكر عند مريض وحيد. The trial included 60 patients(52males,8females) with bladder cancer (mean age: 62.5 years).The majority were chain smokers (70%). They suffered hematuria (100%) and voiding obstructive symptoms (75%). They were diagnosed by cystoscopy. We noticed a small tumor in 58% and multiple tumors in 60%. There were Ta, T1, T2, T3 and T4 in 36%, 31%, 25%, 6.6%, respectively. There were G1, G2, G3 in 38%, 43%, 18% ;respectively. The TUR–BT was performed in 66% of the cases with intravesical adjuvant chemotherapy, and the radical cystectomy was performed for 28% and in 3% of cases we performed a partial cystectomy. The Ureterosigmoidostomy was performed for 7 patients, and the orthotropic urinary diversion was performed in 6 cases. The Cutaneous Ureterostomy was performed for 2 patients and we performed a1Continent Cathaterizable Reservoir and a 1 Bricker's procedure.